Inclusive Fitness of Male and Facultatively Social Female Nesting Behavior in the Socially Polymorphic Bee, Ceratina australensis (Hymenoptera: Xylocopinae). (8th September 2020) - Oppenheimer, Robert L; Rehan, Sandra M
Abstract: Male hymenopterans do not typically provide help with nest construction or maintenance. This is thought to be due to the decreased relatedness of males to their siblings compared to sisters, and selection for outbreeding resulting in male dispersal from natal nesting sites. However, some instances of male 'helping' behaviors have been observed and can usually be explained by increased access to mating with resident females. Here we report on the first observations of cohabiting males within the nests of reproductive females of the facultatively social small carpenter bee, Ceratina australensis . Social nesting in C. australensis occurs at a consistently low rate across populations. We used microsatellites markers to determine relatedness, combined with 3 yr of nest demographic data collected across three populations, to assess the relative fitness of reproductive, nonreproductive, and male individuals cohabiting in reproductive nests. We found that males were brothers of reproductive females, both remaining in their natal nest. However, there was no evidence that they were mating with their sisters across all nests observed. Males in reproductive nests did not gain any direct or indirect fitness benefits as they did not sire any brood and their presence did not increase brood productivity or survivorship. It is possible that males were waiting to mate with nieces who had not yet emerged. Why males were tolerated remains unknown. Mating biology is an important consideration in social theory which requires additional empirical studies. Future long-term studies are needed to capture unusual social behaviors including male nesting behaviors.